SISTEM INFORMASI DESA MENGGUNAKAN TELEGRAM BOT SEBAGAI ANTAR MUKA - Sibero, Alexander F.K.; Murdani, Aderia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
The village information system is a system that supports the implementation of activities at the village office. Technological developments are having a positive impact on how researchers and governments develop software that makes human jobs (in this case, citizens) easier. Village Information System breakthroughs continue to evolve from web-based applications to applications running on instant messaging platforms. Automated answering telegrams, bots and robots are also constantly being developed so that they can be used to support human work. Telegram Bot and Webhook were developed as part of an autoresponder. The task of this automated answering machine is to replace administrative tasks normally performed by humans. Telegram bot and webhook development using Google Script as the language for building APIs tries to find programming solutions outside of the popular programming languages ​​among application developers. The results of this research will benefit users, especially integrated village communities and village organizations.